2009
DOI: 10.1088/0264-9381/26/19/195009
|View full text |Cite
|
Sign up to set email alerts
|

Induced vacuum current and magnetic field in the background of a cosmic string

Abstract: Vacuum polarization effects in the cosmic string background are considered. We find that a current is induced in the vacuum of the quantized massive scalar field and that the current circulates around the string which is generalized to a (d − 2)-brane in locally flat (d + 1)-dimensional space-time. As a consequence of the Maxwell equation, a magnetic field strength is also induced in the vacuum and is directed along the cosmic string. The dependence of the current and the field strength on the string flux and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…2 Additionally to the contribution for the energy-momentum tensor associated with charged quantum fields, the presence of a magnetic flux along the cosmic string induces vacuum current densities, as well. This phenomenon has been investigated for massless scalar field in [28] and recently for massive one in [29]. There the authors have shown that a vacuum induced azimuthal current densities, j ϕ , take place if the ratio of the magnetic flux by the quantum one has a non-vanishing fractional part.…”
Section: Introductionmentioning
confidence: 98%
“…2 Additionally to the contribution for the energy-momentum tensor associated with charged quantum fields, the presence of a magnetic flux along the cosmic string induces vacuum current densities, as well. This phenomenon has been investigated for massless scalar field in [28] and recently for massive one in [29]. There the authors have shown that a vacuum induced azimuthal current densities, j ϕ , take place if the ratio of the magnetic flux by the quantum one has a non-vanishing fractional part.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of a magnetic flux induces also vacuum current densities. This phenomenon was analyzed for massless [33] and massive [34] scalar fields. It has been shown that an azimuthal vacuum current appears if the ratio of the magnetic flux by the quantum one has a nonzero fractional part.…”
Section: Introductionmentioning
confidence: 99%
“…To construct the complete set of the wave-functions we will consider (13) in the regions r < a and r > a, separately. For the inner region, we have three different configurations of magnetic field given by (5)- (9), as we showed previously.…”
Section: The Geometry and The Fermionic Wave-functionsmentioning
confidence: 99%
“…Consequently, there will be three different solutions for (13). Let us define each radial function represented by R (i) l , where we introduced i = 1, 2, 3, the index associated with the model and l = 1, 2 the index associated to the spinor components.…”
Section: The Geometry and The Fermionic Wave-functionsmentioning
confidence: 99%
See 1 more Smart Citation